Embedding robotic surgery into routine practice and impacts on communication and decision making: a review of the experience of surgical teams. Issue 2 (May 2016) - Randell, Rebecca; Honey, Stephanie; Alvarado, Natasha; Pearman, Alan; Greenhalgh, Joanne; Long, Andrew; Gardner, Peter; Gill, Arron; Jayne, David; Dowding, Dawn
Abstract While an increasing number of healthcare providers are purchasing surgical robots because of anticipated improvements in patient outcomes, their implementation into practice is highly variable. In robotic surgery, the surgeon is physically separated from the patient and the rest of the team with the potential to impact communication and decision making in the operating theatre and subsequently patient safety. Drawing on the approach of realist evaluation, in this article we review reports of the experience of surgical teams that have introduced robotic surgery to identify how and in what contexts robotic surgery is successfully integrated into practice and how and in what contexts it affects communication and decision making. Our analysis indicates that, while robotic surgery might bring about a number of benefits, it also creates new challenges. Robotic surgery is associated with increased operation duration, which has implications for patient safety, but strategies to reduce it can be effective with appropriate support from hospital administration and nursing management. The separation of the surgeon from the team can compromise communication but may be overcome through use of standardised communication. While surgeon situation awareness may be affected by the separation, the ergonomic benefits of robotic surgery may reduce stress and tiredness and enhance surgeon decision making. Our review adds to the existing literature by revealing strategies to support the introduction of robotic surgery and contextual factors that need to be in place for these to be effective.